The state, antisemitism, and collaboration in the Holocaust : the borderlands of Romania and the Soviet Union - Dumitru, Diana (Cambridge University Press, 2016)
"Based on original sources, this important new book on the Holocaust explores regional variations in civilians' attitudes and behavior toward the Jewish population in Romania and the occupied Soviet Union. Gentiles' willingness to assist Jews was greater in lands that had been under Soviet administration during the inter-war period, while gentiles' willingness to harm Jews occurred more in lands that had been under Romanian administration during the same period. While acknowledging the disasters of Communist rule in the 1920s and 1930s, this work shows the effectiveness of Soviet nationalities policy in the official suppression of antisemitism. This book offers a corrective to the widespread consensus that homogenizes gentile responses throughout Eastern Europe, instead demonstrating that what states did in the interwar period mattered; relations between social groups were not fixed and destined to repeat themselves, but rather fluid and susceptible to change over time"--